Suppression of autophagy and antigen presentation by Mycobacterium tuberculosis PE_PGRS47 (2016)
ABSTRACT: Suppression of major histocompatibility complex (MHC) class II antigen presentation is believed to be among the major mechanisms used by Mycobacterium tuberculosis to escape protective host immune responses. Through a genome-wide screen for the genetic loci of M. tuberculosis that inhibit MHC class II-restricted antigen presentation by mycobacteria-infected dendritic cells, we identified the PE_PGRS47 protein as one of the responsible factors. Targeted disruption of the PE_PGRS47 (Rv2741) gene led to attenuated growth of M. tuberculosis in vitro and in vivo, and a PE_PGRS47 mutant showed enhanced MHC class II-restricted antigen presentation during in vivo infection of mice. Analysis of the effects of deletion or over-expression of PE_PGRS47 implicated this protein in the inhibition of autophagy in infected host phagocytes. Our findings identify PE_PGRS47 as a functionally relevant, non-redundant bacterial factor in the modulation of innate and adaptive immunity by M. tuberculosis, suggesting strategies for improving antigen presentation and the generation of protective immunity during vaccination or infection. Mycobacterium tuberculosis (Mtb) persists within mammalian hosts through a variety of immune evasion strategies, including the inhibition of multiple antigen presentation pathways that are central to adaptive immunity1. Major histocompatibility complex (MHC) class II molecules, which control CD4+ T-cell responses, are critical for host resistance to Mtb, and the bacilli have evolved the ability to modulate the expression and function of these molecules2–8. Autophagy is a ubiquitous cellular process that participates in the processing of antigens for MHC class II antigen presentation9–12, and in cells infected by vacuolar pathogens like Mtb it provides a potential mechanism to initiate phagosome maturation and enhance the processing and presentation of their antigens to T cells12–14. Recent evidence suggests that Mtb has developed immune evasion strategies that interfere with autophagy, thus improving its intracellular survival and limiting the presentation of its antigens by MHC class II. Although several mycobacterial factors have been implicated in this aspect of immune evasion15–17, the mechanisms and specific mediators involved remain mostly unknown. In the current study, we undertook a genome-wide gain of function screen to identify genes of Mtb involved in the inhibition of MHC class II presentation in Mtb-infected cells. This identified at least five genomic loci of Mtb that independently contribute to the inhibition of MHC class II-restricted antigen presentation, several of which also blocked autophagy. Detailed analysis of one of these loci implicated PE_PGRS47, a member of a large family of virulence-related genes in Mtb, as an inhibitor of autophagy and a factor contributing to evasion of both innate and adaptive immunity by Mtb. These findings identify a specific mycobacterial factor involved in the evasion of innate and adaptive immunity against Mtb and provide new insight into the role of PE_PGRS proteins in tuberculosis.